Pengaruh Program Pembangunan Pemberdayaan dan Pembinaan Dana Desa Terhadap Kesejahteraan Masyarakat Di Kecamatan Babussalam Kabupaten Aceh Tenggara - Ilham Eka Putra; Erlina Erlina; Sirojuzilam Sirojuzilam (Jurnal Intervensi Sosial dan Pembangunan, 2023)
The aims of this study were to analyze the influence of the Development Program on the welfare of the people in Babussalam District, Southeast Aceh Regency. To analyze the effect of the Empowerment Program on people's welfare in Babussalam District, Southeast Aceh Regency. To analyze the influence of the Development Program on the welfare of the people in Babussalam District, Southeast Aceh Regency. The research was conducted in Southeast Aceh District on the Influence of Village Fund Development, Empowerment and Development Programs on Community Welfare in Babussalam District, Southeast Aceh District. The analytical method used in this study is multiple regression analysis with a total of 314 respondents. The results of the study showed that: the Development Program has a significant effect on the welfare of the people in Babussalam District, Southeast Aceh Regency. The Empowerment Program has a significant effect on the welfare of the people in Babussalam District, Southeast Aceh Regency. The Coaching Program has a significant effect on the welfare of the people in Babussalam District, Southeast Aceh Regency.Keywords: Development Program, Empowerment and Development of Village Funds, community welfare